USING ASYMMETRIC DISTRIBUTIONS FOR MODELING GENE EXPRESSION DATA - MACERAU, Walkiria Maria de Oliveira; MILAN, Luis Aparecido (Brazilian Journal of Biometrics, 2021)
We present a short review of the asymmetric distributions alpha-stable, skew normal, skew Student’s t and skew Laplace. We compare the performance for these distributions, in general, are used to model asymmetric data, using AIC and BIC. These criterias were able to selecting the best model for each data set. We also apply these models to gene expression data and we verify these distributions are qualified to model these observations.